Uji Reduksi Methylene Blue pada Susu Segar di Kelompok Peternak Sapi Perah Dusun Pabyongan Kabupaten Tulungagung - Andyanita Hanif Hermawati; Hariyanto Hariyanto; Aulia Zahratul Husna (Borneo Journal of Medical Laboratory Technology, 2021)
Milk is a food that has complete and perfect nutrition. The main product produced by dairy cows is livestock. In Tulungagung there are several dairy farming areas, including the Pabyongan hamlet. The purpose of this study was to analyze the reduction test using methylene blue 1% in fresh milk in the dairy farmer group of Pabyongan Tulungagung hamlet. This research is a qualitative descriptive design with the Simple Random Sampling technique. The results of this study indicate that from a total of 10 fresh milk samples, it is known that 9 fresh milk samples (90%) have a good reduction test and 1 fresh milk sample (10%) has a bad reduction test. Based on the results of the above research, it can be stated that 90% of the fresh milk samples from the dairy farmer group in Pabyongan Pagerwojo village have a good reduction test. Poor reduction test results are due to the condition of the cage is not clean, the condition of the animal being sick, the condition of the farmer being sick, or the equipment is not clean.